(untitled) (Symposium on Life and Environmental Sciences, 2026)
The growing urgency of environmental challenges has placed “green skills” – competencies for sustainable development, circular economy, and ecological citizenship – at the core of modern education. This article examines the socio-pedagogical mechanisms that enable the effective formation of green skills within environmental education. It integrates insights from social constructivism, experiential learning theory, and community-based education to propose a multi-level framework. Key mechanisms include: curriculum integration across disciplines, project-based and place-based learning, teacher professional development, multi-stakeholder partnerships, and digital tools for environmental action. The article argues that sustainable green skills formation requires systemic alignment of pedagogical approaches, institutional culture, and authentic societal engagement.